PENGARUH UKURAN KANTOR AKUNTAN PUBLIK, PROFITABILITAS, SOLVABILITAS, AUDIT TENURE DAN UKURAN PERUSAHAAN TERHADAP AUDIT DELAY (Studi Empiris pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023) - Jauhariah, Siti; Azlina, Nur; Nurulita, Suci (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2025)
This study aims to examine the Effect of Public Accounting Firm Size, Solvency, Profitability,Audit Tenure and Company Size on Audit Delay in Mining Companies Listed on the IndonesiaStock Exchange in 2019-2023. In this study, the sample population was 34 companies, for 5years, calculated from 2019 to 2023 so that the number of observations was 150 samples.Sampling used Purposive Sampling. Data analysis used in this study used multiple regressionanalysis techniques with a statistical approach operated through the SPSS program. Theresults of this study concluded that Public Accounting Firm Size and Profitability did not havea significant effect on Audit Delay. While Solvency, Audit Tenure and Company Size had asignificant effect on Audit Delay in Mining Companies Listed on the Indonesia Stock Exchangein 2019-2023.Keywords: Public Accounting Firm Size, Profitability, Solvency Audit Tenure, Company Size,Audit Delay